Suppression of diet-induced atherosclerosis in low density lipoprotein receptor knockout mice overexpressing lipoprotein lipase. - Shimada, M (1996)
Lipoprotein lipase (LPL) is a key enzyme in the hydrolysis of triglyceride-rich lipoproteins. Conflicting results have been reported concerning its role in atherogenesis. To determine the effects of the overexpressed LPL on diet-induced atherosclerosis, we have generated low density lipoprotein receptor (LDLR) knockout mice that overexpressed human LPL transgene (LPL/LDLRKO) and compared their plasma lipoproteins and atherosclerosis with those in nonexpressing LDLR-knockout mice (LDLRKO). On a normal chow diet, LPL/LDLRKO mice showed marked suppression of mean plasma triglyceride levels (32 versus 236 mg/dl) and modest decrease in mean cholesterol levels (300 versus 386 mg/dl) as compared with LDLRKO mice. Larger lipoprotein particles of intermediate density lipoprotein (IDL)/LDL were selectively reduced in LPL/LDLRKO mice. On an atherogenic diet, both mice exhibited severe hypercholesterolemia. But, mean plasma cholesterol levels in LPL/ LDLRKO mice were still suppressed as compared with that in LDLRKO mice (1357 versus 2187 mg/dl). Marked reduction in a larger subfraction of IDL/LDL, which conceivably corresponds to remnant lipoproteins, was observed in the LPL/LDLRKO mice. LDLRKO mice developed severe fatty streak lesions in the aortic sinus after feeding with the atherogenic diet for 8 weeks. In contrast, mean lesion area in the LPL/LDLRKO mice was 18-fold smaller than that in LDLRKO mice. We suggest that the altered lipoprotein profile, in particular the reduced level of remnant lipoproteins, is mainly responsible for the protection by LPL against atherosclerosis.